A Multidisciplinary Hospital-based Antimicrobial Use Program: Impact on Hospital Pharmacy Expenditures and Drug Use - Suzette Salama; Coleman Rotstein; Lionel Mandell (Canadian Journal of Infectious Diseases)
The authors’ hospital embarked on a three-component, multidisciplinary, hospital-based antimicrobial use program to cut costs and reduce inappropriate antimicrobial use. Initially, antimicrobial use patterns and costs were monitored for 12 months. For the next two years, an antimicrobial use program was implemented consisting of three strategies: automatic therapeutic interchanges; antimicrobial restriction policies; and parenteral to oral conversion. The program resulted in a reduction in the antimicrobial portion of the total pharmacy drug budget from 41.6% to 28.2%. Simultaneously, the average cost per dose per patient day dropped from $11.88 in 1991 to $10.16 in 1994. Overall, mean monthly acquisition cost savings rose from $6,810 in 1992 to $27,590 in 1994. This study demonstrates that a multidisciplinary antimicrobial use program in a Canadian hospital can effect dramatic cost savings and serve as a quality assurance activity of physician antimicrobial prescribing behaviour.